Efektivitas Kombinasi Sport Massage dan Infra Red terhadap Cedera Pergelangan Tangan - Muhbaedillah, Habil; Muhtar, Tatang; Rukmana, Anin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to determine the success rate of the combination of sports massage and infrared light in increasing range of motion (ROM) after wrist injury. This research is a pre-experimental design research with a one-group pretest-posttest design. The population in this study was Badminton UKM, Basketball UKM, volleyball UKM, and Indonesian Education University. The results of this research after treatment was given to the research subjects showed that the extension segment had a value of t= -10.598, flexion had a value of t= -9.355, abduction had a value of t= -11.667, adduction had a value of t= -12.894 with a significance value of 0.00 < 0.05 if < 0.05, then it can be concluded that H1 is accepted. In conclusion, there is a significant influence on the results of the combination of sports massage and infrared on the range of motion of wrist injuries.. Keyword: Sport massage, Infra red, Range Of Motion, Wrist Injury